Deservingness and Punishment in Juvenile Justice: Do Black Youth Grow Up “Faster” in the Eyes of the Court? - Zane, Steven N. (Youth violence and juvenile justice, 2022)
The present study investigated whether race moderates the effect of age on juvenile court dispositions in ways that illuminate a subtler form of racial disparities than has been previously identified. Drawing on prior theory and research, we hypothesize that at young ages, virtually all youth are perceived as children and met with treatment-oriented responses. As youth grow older, however, we anticipate that Black defendants will be perceived as more culpable and more deserving of punishment than similarly-aged White defendants and that disposition patterns will reflect that differential perception. Using data from the Florida Department of Juvenile Justice (N = 124,075), the present study examines a five-category disposition using a multinomial regression model with interactions between age and race variables. We found mixed support for the hypotheses. On the one hand, compared to similarly-aged White defendants, Black defendants became significantly less likely to be diverted—the most treatment-oriented disposition—and significantly more likely to be transferred—the most punitive disposition—as age increased. On the other hand, race did not moderate age effects for dismissal, probation, or commitment. There is thus some evidence that age may be racialized for some dispositions, but not others. Implications for research and policy are discussed.